Natural-linewidth measurements of the 3𝐶 and 3⁢𝐷 soft-x-ray transitions in Ni xix - Shah, Chintan; Kühn, Steffen; Bernitt, Sonja; Steinbrügge, René; Togawa, Moto; Berger, Lukas; Buck, Jens; Hoesch, Moritz; Seltmann, Jörn; Kozlov, Mikhail G.; Porsev, Sergey G.; Gu, Ming Feng; et al. (Physical review, 2024)
We used the monochromatic soft-x-ray beamline P04 at the synchrotron-radiation facility PETRA III to resonantly excite the strongest 2⁢𝑝−3⁢𝑑 transitions in neonlike Ni xix ions, [2⁢𝑝6]𝐽=0→[(2⁢𝑝5)1/23⁢𝑑3/2]𝐽=1 and [2⁢𝑝6]𝐽=0→[(2⁢𝑝5)3/23⁢𝑑5/2]𝐽=1, respectively dubbed 3⁢𝐶 and 3⁢𝐷, achieving a resolving power of 15 000 and signal-to-background ratio of 30. We obtain their natural linewidths, with an accuracy of better than 10%, as well as the oscillator-strength ratio 𝑓⁡(3⁢𝐶)/𝑓⁡(3⁢𝐷)=2.51⁢(11) from analysis of the resonant fluorescence spectra. These results agree with those of previous experiments, earlier predictions, and our own advanced calculations.
Gesehen am 20.02.2025